Method for router online security risk assessment quantification - Jun-gang YANG; Li LIANG; Gu-jing LIU; Qian ZHANG; Chang-qing ZHANG (Tongxin xuebao)
The concept of router safety performance was proposed based on the nature of router security issues and router attacks were classified. Then a method for router online security risk assessment quantification was also presented.The security risk factor of service decline was calculated by router bandwidth consumption and average CPU usage and the security risk factor of privilege escalation was calcu ated by the possibility of threat occurrence and severity based on the router attack classification. The router security threat status was evaluated combining weighting the importance of router and the security risk factor. The experiment results show the method is effective in calculating the quantitive risk of the router and helpful for administrators to assess security risks.